Architects’ professional perspectives on child- and family-friendly apartment design in Australia - Richard Tucker; Fiona Andrews; Louise Johnson; Jasmine Palmer (Journal of Asian Architecture and Building Engineering)
In recent decades, increasing numbers of families with children are living in apartments in Australian cities; negotiating family life in dwellings not designed for their specific needs. This paper describes indirect participatory design research, involving architects and researchers acting as intermediates of end users, identifying how architects see that apartment design guidelines could be reconciled with the needs of families with children. Architects in Victoria, Australia, participated in a design workshop that elicited their views on child and family needs elucidated by research with families, explored Australian and international apartment design guidelines in relation to families, and which asked in light of this evidence – what needs to change in design guidelines to inform family-friendly apartment designs? Findings reveal important similarities and critical differences between architects’ and users’ views on apartment design for families with children. The paper concludes by discussing how these differences might be reconciled to ensure future apartment designs that suit a more diverse mix of households, including families with children. The challenges are also highlighted of using indirect participatory design when direct participatory design is not possible, including sacrificing the design consensus arising from architects and end users working together.